Chefs seek to win first Gilroy Garlic Bowl title - Uribes, Tom::::::::: (2013)
Fresno State Executive Chef Erik Debaude and his sous chef, alumnus Bryan Kramer, square off this week against chefs from two other universities in a new garlic competition at the 35th Gilroy Garlic Festival's Cook-Off Theater.